Outlawing sexual violence: rape law and the likelihood of civil war. Issue 2 (2nd September 2017) - Avdan, Nazli; Asal, Victor
Abstract: An expanding body of literature maintains that gender inequality heightens the probability of intrastate conflict by creating a structure of violence. The paper proposes the legal system as the missing link between social norms and conflict occurrence. Gender neutrality of the penal code coheres with norms of equality and, further, embodies egalitarian, progressive values associated with pacific norms of conflict resolution. The criminalization of rape enhances female empowerment by offering a legal commitment on the part of the state to safeguard women's physical security. More broadly, legal prohibitions against rape protect women and other vulnerable individuals from sexual aggression. The statistical analysis uses novel data on rape legislation for 194 states over the 1965 to 2005 time period. The length of punitive sentence proxies for the stringency of rape legislation. The empirical findings demonstrate that longer punitive sentences against rape crimes are associated with a significantly lower probability of intrastate conflict. Sanctions against both female and male perpetrators of rape are analyzed separately. The results show that gender neutrality of law whereby the penal code establishes similar sentences for female and male offenders alike also significantly decreases conflict propensity.